2019
DOI: 10.1016/s2214-109x(19)30077-4
|View full text |Cite|
|
Sign up to set email alerts
|

Task sharing with non-physician health-care workers for management of blood pressure in low-income and middle-income countries: a systematic review and meta-analysis

Abstract: Background Task sharing for the management of hypertension could be useful for understaffed and resource-poor health systems. We assessed the effectiveness of task-sharing interventions in improving blood pressure control among adults in low-income and middle-income countries. Methods We searched the Cochrane Library, PubMed, Embase, and CINAHL for studies published up to December 2018. We included intervention studies involving a task-sharing strategy for management of blood pressure and other cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
145
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(168 citation statements)
references
References 89 publications
2
145
0
3
Order By: Relevance
“…After a very acclaimed performance on improving maternal and child health [63], new evidence suggests that community health workers could potentially work as the frontline cadres to ght against the burden of NCDs, including hypertension [64]. Task sharing, particularly with other non-physician health workers in understaffed and resource-poor settings, is an effective strategy for the management of hypertension [31]. Additionally, other approaches such as including pharmacists and nurses in a team and providing team-based hypertension care also showed positive effects on controlling high blood pressure [32].…”
Section: Discussionmentioning
confidence: 99%
“…After a very acclaimed performance on improving maternal and child health [63], new evidence suggests that community health workers could potentially work as the frontline cadres to ght against the burden of NCDs, including hypertension [64]. Task sharing, particularly with other non-physician health workers in understaffed and resource-poor settings, is an effective strategy for the management of hypertension [31]. Additionally, other approaches such as including pharmacists and nurses in a team and providing team-based hypertension care also showed positive effects on controlling high blood pressure [32].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the outcomes of our cohort with those of "similar" cohorts would at first sight be interesting even if not needed. A reliable comparison, however, would be impossible and probably inappropriate, not only because of the rarity of field studies with comparable designs [10][11][12][13], but even more because the unavoidable variability of the nonmedical variables and the settings of care weigh more and are closer to reality than measures standardized and imposed in a formal comparative protocol. The parallel work in Ecuador on the incoherence and irrelevance for Latin America of protocols recommended by international groups based on E.U.…”
Section: Lowmentioning
confidence: 99%
“…Observational studies of CHW-led interventions demonstrated improvement in fasting plasma glucose,8 9 though a recent cluster-randomised trial found inconclusive results, potentially due to a lack of power 10. For cardiovascular disease, two systematic reviews, including one meta-analysis of randomised trials, identified improvements in blood pressure with CHW interventions 4 11. Several recent cluster-randomised trials around the world demonstrated blood pressure reduction and improved cardiovascular risk control among patients with uncontrolled hypertension 10 12–15.…”
Section: Introductionmentioning
confidence: 99%